Perbandingan Metode Preparasi Sampel pada Penetapan Kadar Protein Tempe Kacang Kedelai dengan Metode Biuret - Koeswara, Thobias Tantra; Auli, Winni Nur; Tursino, Tursino (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2024)
The determination of protein content in food commonly uses the Kjeldahl method. This method assumes the presence of total nitrogen. The Kjeldahl method is considered not only to measure the nitrogen content of proteins. Therefore, in this study, the Biuret method was used. However, this method can only be used on samples in the form of solutions. Thus, an appropriate sample preparation method is required to obtain the final sample preparation product in the form of a solution. This study aimed to determine the effect of sample preparation methods on measured protein content and to give recommended sample preparation methods. The principle of the Biuret method in determining protein content based on Cu2+ complex formation with peptide bonds obtained the maximum wavelength of 548 nm. In this study, four preparation methods were used. The first method is based on protein precipitation using trichloro acetic acid 10%; the second method principle is precipitation by ammonium sulfate and acetate buffer; the third method uses 10% NaOH to dissolve the protein, then precipitated using H2SO4 10%; the principle of the fourth method is to dissolve the protein with 1 M NaOH and heating to reduce protein particles. The specified testing parameters are protein content, cost, and simplicity. The protein content in each method was obtained respectively: 12,5% (±0,012), 6,0% (±0,006), 10,2% (±0,001), and 16,1% (±0,216). In conclusion, sample preparation methods affect protein content. The fourth method is the best for giving protein content that complies with SNI. Other than that, the fourth method is cheaper, more straightforward, and more simple compared to the other three preparation methods.